Pengaruh Disiplin Kerja dan Kemampuan Kerja Terhadap Prestasi Kerja Pegawai pada Kantor Badan Kependudukan dan Keluarga Berencana Nasiona (BKKBN) Kota Bima - Abdurrahim Abdurrahim; Firmansyah Kusumayadi; Kartin Aprianti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the influence of work discipline and work ability on the work performance of employees at the Office of the National Population and Family Planning Agency (BKKBN) of Bima City. The research method used is a quantitative approach with survey techniques. Data was collected through a questionnaire distributed to Bima City BKKBN employees. The results of the study show that work discipline and work ability significantly affect employee work performance. Good work discipline can improve employee performance, while adequate work skills also make a positive contribution to work performance. This finding provides practical implications for BKKBN management in an effort to improve employee work performance through strengthening discipline and developing work skills.